2009
DOI: 10.1111/j.1467-9523.2009.00495.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Trust on West Australian Farmers' Responses to Infectious Livestock Diseases

Abstract: Globalisation has rendered the island nation of Australia more vulnerable to infectious livestock diseases, making bio-security a key concern of government. Although farmers are at the front line of disease surveillance, little is known about this group's behaviour and motives. A study to investigate on-farm bio-security practices -and in particular how farmers decide whether to report unusual symptoms in their livestock -was conducted with sheep and cattle producers in Western Australia. This article reports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
76
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 24 publications
(59 reference statements)
6
76
0
1
Order By: Relevance
“…Results of a qualitative study among Australian sheep farmers on implementing biosecurity measures (Palmer et al, 2007) showed that one of the basic issues that may underlie the problem of not reporting clinically suspect situations to either the local agricultural department office or even a veterinarian may be a low level of trust in the government as well as agricultural extension agents. This lack of trust in government bodies also appeared as an important factor why farmers do not trust government information on improving biosecurity measures (Heffernan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Results of a qualitative study among Australian sheep farmers on implementing biosecurity measures (Palmer et al, 2007) showed that one of the basic issues that may underlie the problem of not reporting clinically suspect situations to either the local agricultural department office or even a veterinarian may be a low level of trust in the government as well as agricultural extension agents. This lack of trust in government bodies also appeared as an important factor why farmers do not trust government information on improving biosecurity measures (Heffernan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Since the early clinical signs of many foreign diseases may be indistinguishable from diseases which are present in the United States, producers also need to understand which animals are most at risk of foreign disease introduction. Studies suggest that producers' perception of the risk of a foreign disease influences their interpretation of clinical signs and willingness to report sick livestock (Palmer et al, 2009;Elbers et al, 2010). Although educational materials, such as pamphlets and websites, are important tools for raising awareness of disease risk, veterinarians are uniquely situated to help producers understand these materials in the context of the producer's own livestock operation.…”
Section: Discussionmentioning
confidence: 99%
“…A study examining the reporting of pigs with clinical signs of classical swine fever in the Netherlands found that factors such as a lack of knowledge of early clinical signs of the disease were important; however, additional factors such as producers' negative opinions of disease control measures, negative emotions associated with going through the reporting process, such as guilt or shame, and a lack of trust in government bodies also appeared to play an important role in influencing reporting (Elbers et al, 2010). A qualitative study of Australian sheep producers found that farmers' decisions regarding reporting and biosecurity measures were often based on the perceived risk to their operation, and that trust in others contributed significantly to perceived risk (Palmer et al, 2009). Garforth et al (2013) developed an analytical framework linking social and psychological factors to producers' disease risk management behavior based on a literature review.…”
Section: Introductionmentioning
confidence: 99%
“…These behaviors represent important targets for risk communication, since enhanced cooperation may reduce the size and severity of an outbreak. Some efforts have been made to understand producers' beliefs about disease reporting or on-farm disease control (Hopp et al, 2007;Heffernan et al, 2008;Palmer et al, 2009;Elbers et al, 2010;Delgado et al, 2012;Alarcon et al, 2014;Garforth et al, 2013) and the consequences of reporting on the severity of an outbreak Carpenter et al, 2011). However, other important producer behaviors which could impact the severity of a disease outbreak have received minimal attention.…”
Section: Introductionmentioning
confidence: 99%